Molecular genotyping reveals inter-regional relatedness among antimicrobial resistant Salmonella Minnesota strains isolated from poultry farm and humans, Brazil - Moreira, João Paulo Fernandes Ferreira; do Monte, Daniel Farias Marinho [UNESP]; Lima, Camila de Aguiar; de Oliveira, Celso José Bruno; da Silva Martins, Nelson Rodrigo; Berchieri Junior, Angelo [UNESP]; de Freitas Neto, Oliveiro Caetano (Springer Nature, 2022)
Genetic profiles of Salmonella Minnesota isolates were analyzed using pulsed-field gel electrophoresis (PFGE). In total, 13 isolates obtained from the broiler industry collected in the states of Minas Gerais (11) and São Paulo (2), as well as five recovered from cases of foodborne infections in humans in the states of Minas Gerais (2), Santa Catarina (1), and Rio Grande do Sul (2), were submitted to PFGE. These 18 S. Minnesota isolates together with other 12 of poultry origin were also subjected to antimicrobial susceptibility testing. The PFGE analysis of 18 strains of S. Minnesota generated a dendrogram that grouped the isolates with 83–90% similarity into four main clusters. Among them, cluster “A” grouped the majority of isolates (13), including two of human origin that showed 90% similarity with a broiler isolate, both recovered in Minas Gerais. The S. Minnesota isolates showed resistance to tetracycline (80%), cefoxitin (80%), ceftazidime (46.7%), nalidixic acid (23.3%), ciprofloxacin (13.3%), and streptomycin (10%). No resistance to gentamicin, chloramphenicol, meropenem, nitrofurantoin, and sulfamethoxazole-trimethoprim was found. Moreover, 23.3% of the evaluated isolates presented multi-resistance profile, all from Minas Gerais. The results highlight the importance of further studies involving S. Minnesota, which is prevalent in the Brazilian broiler flocks and could provoke foodborne infection in humans.
Keywords: Foodborne infection; Multi-resistance; PFGE; Public health; Salmonellosis